Advances in Analytical Methods for Erythropoietin Identification: From Clinical Use to Anti-Doping Applications: From Clinical Use to Anti-Doping Applications - Schafer, Matheus Betat; Santos , Bruno Pereira dos; Arbo, Marcelo Dutra (Drug Analytical Research, 2026)
Erythropoietin (EPO) is an endogenous glycoprotein essential for erythropoiesis regulation and is produced mainly by the kidneys and to a lesser extent by the liver. Its synthesis is stimulated by hypoxia and regulated by a complex feedback system. Endogenous EPO has 165 amino acids and plays a critical role in the survival, proliferation, and differentiation of erythroid progenitor cells through intracellular signaling pathways such as JAK2/STAT5, MAPK/ERK, and PI3K/AKT. Recombinant erythropoietin (rhEPO), produced in CHO cells using recombinant DNA technology, share the structure and biological activity of endogenous EPO and is widely used to treat anemia associated with chronic kidney disease, chemotherapy, chronic inflammatory diseases, and HIV/AIDS. It is also administered in elective surgery to reduce transfusion needs. However, rhEPO is misused in sports doping because it increases red blood cells, enhances oxygen delivery and physical performance. This misuse is common in endurance sports and presents technical, ethical, and medical concerns. To address this, analytical methods—including isoelectric focusing, SDS-PAGE, and isoform profiling—have been developed to detect exogenous EPO. Nevertheless, these techniques still face challenges related to sensitivity, microheterogeneity, and overlapping between endogenous and recombinant forms. This work reviews the biochemical, clinical, and technological aspects of erythropoietin, emphasizing analytical strategies for its detection, therapeutic applications, and ongoing challenges in anti-doping contexts.